Terapeutski efekat dva fluoridna laka na remineralizaciju lezija belih tačaka registrovan laserskom fluorescencijom - Knežević, Ranka; Vojinović, Jovan (Scripta Medica, 2022)
Background / Aim: The presence of white spot lesion (WSL) is considered the first stage of dental caries. The early detection and diagnosis of WSL is of crucial importance, since caries can be prevented at this stage, reversed and/or controlled by elimination of etiological factors and by use of fluorides. The aim of this study was to compare the efficacy between the two fluoride varnishes on WSL remineralisation evaluated by laser fluorescence.Methods: A total of 30 children and 60 WSL cases (2 per each child) were included in this study. The selected WSL were randomly divided into two groups in each child: G1 applying Fluor Protector S®, Vivadent, Lichenstein (n = 30) and G2 applying MI varnish®, GC, Tokyo, Japan (n = 30). The fluoride varnishes were submitted to three applications: at baseline, four weeks and eight weeks following the baseline, according to the manufacturer's recommendations. Mineral density of the enamel was measured using laser fluorescence (DIAGNOdent® 2095, KaVo, Biberach, Germany) for each WSL. Laser fluorescence (LF) measurementswere performed at baseline and at fourth, eighth and twelfth week after starting the treatment and LF scores were calculated.Results: By comparing LF scores at each measurement after treatment initiation, it was found that the scores were significantly lower in all groups when compared to baseline.Conclusion: The results of this study indicate that both fluoride varnishes used were capable of remineralising WSL as evaluated by LF measurements. No difference was noted in the remineralising efficacy of the varnishes despite their different compositions. The main limitations of this study are small sample sizeand short follow up period. Therefore, further studies with large sample size and a longer follow up are, however, necessary.